Wahdah Islamiyyah Palu: on Contemporary Islamic Legal Issues In The Internet - Rusli Rusli (State Institute of Islamic Studies (IAIN) Palu, 2017)
This paper deals with one of the Islamic organizations in Palu, Wahdah Islamiyah (Islamic Unity), in terms of theological and contemporary Islamic legal issues. The source of analysis is the website that Wahdah Islamiyah runs online. The paper concludes that Wahdah Islamiyah is influenced by the relatively strict theology of Wahhābism in religiosity and morality. Therefore, in legal issues, Wahdah Islamiyah embraced and accommodated relatively conservative views with various issues in relation to theological issues and Islamic legal issues such as women’s, social, economic, and political issues. From these views, it can be argued that their aim is to preserve the identity by constructing the concepts of shirk and bidʻah and reinforcing the relatively rigid juristic tradition to become the citadel from the attacks of doctrine seeking to demolish the building of Salafism.